Legitimacy: Yugoslav lessons for Ukraine - Vladimir Gligorov (The Vienna Institute for International Economic Studies (wiiw), 2016)
Examples from the breakup of Yugoslavia and state-building in the successor states are used to highlight the political and constitutional choices facing Ukraine. The main lesson is that legitimacy is needed for constitution-building, which is needed for long-term state stability. Ethnic and other diversities are not crucially important except if they are used as a means for external interference.
Keywords: H10; H77; K100; F510; 330; Legitimacy; democracy; constitutionalism; international intervention; state building